Comparison Between A* And Obstacle Tracing Pathfinding In Gridless Isometric Game - Lailatul Husniah; Rizky Ade Mahendra; Ali Sofyan Kholimi; Eko Budi Cahyono (IAES Indonesia Section, 2018)
The pathfinding algorithms have commonly used in video games. City 2.5 is an isometric grid-less game which already implements pathfinding algorithms. However, current pathfinding algorithm unable to produce optimal route when it comes to custom shape or concave collider. This research uses A* and a method to choose the start and end node to produce an optimal route. The virtual grid node is generated to make A* works on the grid-less environment. The test results show that A* be able to produce the shortest route in concave or custom obstacles scenarios, but not on the obstacle-less scenarios and tight gap obstacles scenarios.